AP2S1 and GNA11 mutations – not a common cause of familial hypocalciuric hypercalcemia. Issue 2 (February 2017) - Hovden, Silje; Rejnmark, Lars; Ladefoged, Søren A; Nissen, Peter H
Abstract : Objective: Familial hypocalciuric hypercalcemia (FHH) type 1 is caused by mutations in the gene encoding the calcium-sensing receptor ( CASR ). Recently, mutations affecting codon 15 in the gene AP2S1 have been shown to cause FHH type 3 in up to 26% of CASR -negative FHH patients. Similarly, mutations in the gene G NA11 have been shown to cause FHH type 2. We hypothesized that mutations in AP2S1 and GNA11 are causative in Danish patients with suspected FHH and that these mutations are not found in patients with primary hyperparathyroidism (PHPT), which is the main differential diagnostic disorder. Design: Cross-sectional study. Methods: We identified patients with unexplained hyperparathyroid hypercalcemia and a control group of verified PHPT patients through review of 421 patients tested for CASR mutations in the period 2006–2014. DNA sequencing of all amino acid coding exons including intron–exon boundaries in AP2S1 and GNA11 was performed. Results: In 33 CASR -negative patients with suspected FHH, we found two ( 6%) with a mutation in AP2S1 (p.Arg15Leu and p.Arg15His). Family screening confirmed the genotype–phenotype correlations. We did not identify any pathogenic mutations in GNA11 . No pathogenic mutations were found in the PHPT control group. Conclusions: We suggest that the best diagnostic approach to hyperparathyroid hypercalcemic patients suspected to have FHH is to screen the CASR and AP2S1 codon 15 for mutations. If the results are negative and there is still suspicion of an inherited condition (i.e. family history), then GNA11 should be examined.